Dança, educação, corpo e ancestralidade: processo de criação em dança antirracista na Escola Municipal Dr. Eloy de Souza, no município de Lajes, RN - Faria, Larissa Araújo de (2024)
The present research aims to show a cartographic study, an anti-racist dance creation process that took place in Escola Municipal Dr. Eloy de Souza, a school located in Lajes, RN. This intervention process reveals pedagogical and transgressive trajectories which is based on the implementation of the law 11.645 at the school environment. At the same time, studies about the importance of the dance to educate and strengthen the transgression of the bodies were done using the contact and improvisation practice, the support we use to create a possibility to construct an autonomous and anti-racist trajectory to the students. Besides, this dissertation is also concerned to map the ancestral and subjective processes of those “bodies-territories” of knowledge, those which dance and tell their own narratives and also have recognized and enhanced memories. This process will happen through experiences and research into afro dances and their nuances, like circularity, weight, directions, movement and pause. All of those points will be experienced through an immersion of contact and improvisation practice to the creation, the game of capoeira and the samba de roda. Supported by education laws and based on dialogue with researchers who build possible paths for anti-racists dance education in their production, this dissertation is concerned to promote a conversation with Freire (2013), Almeida (2019), Muzanga (2005), Fanon (2018), Moura (2018), Porpino (2018), Oliveira (2005), Santos (2021) and Hooks (2013). The research will go trough the field of sensitivity and subjectivity, the production and recognition of the afro-diasporic ancestral memory of the bodies, to build a process of creating the geographic exhibition, which will be presented to the school community.